Symbolic Ownership, Limited Control: An Intersectional Socio-Legal Study of Minangkabau Women and Ancestral Property - Rizky, Farah Futhihat (Universitas Islam Negeri Alauddin Makassar, 2026)
This study examines how Minangkabau women, as normative heirs of harta pusaka tinggi (ancestral communal property), experience the management of inheritance within Indonesia’s plural legal context. Although Minangkabau adat institutionalizes matrilineal transmission and communal ownership of ancestral property, empirical realities show persistent disputes and unequal decision-making practices shaped by informal customary authority. Employing an empirical socio-legal research design with a qualitative approach, this study draws on in-depth, semi-structured interviews with three Minangkabau women heirs (conducted on 5 and 10 December 2024), complemented by observation and documentation, and supported by secondary and tertiary legal sources. The findings reveal a structural gap between normative recognition and lived practice: women are culturally positioned as custodians of the rumah gadang and customary land, yet substantive control over strategic decisions particularly the utilization of pusaka tinggi often remains dominated by mamak and male clan authorities. Women’s experiences are not uniform; differences in social class and education shape their bargaining capacity, ranging from subsistence-oriented use of rice fields to more formalized management supported by economic and legal literacy resources. Moreover, women bear layered burdens across domestic care work, productive labor, and customary obligations, which can intensify vulnerability despite matrilineal legitimacy. This study contributes to socio-legal debates on legal pluralism and gender justice by demonstrating that matrilineal inheritance may reproduce inequality through informal customary power. The study concludes that strengthening gender-just governance of pusaka tinggi requires more transparent customary mechanisms, enhanced customary legal literacy for women, and written procedures regulating the use of ancestral property by mamak to reduce unilateral practices and potential conflict.